2011
DOI: 10.4103/0973-6131.85491
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and pattern of stress relaxation practices in Ahmedabad city: A cross-sectional study

Abstract: Background:Research has shown the growing importance of stress relaxation practices (SRPs) in many noncommunicable diseases. But there is little information on the prevalence of SRPs in Indian population.Objectives:To study the prevalence of different types of SRPs and their sociodemographic profile.Materials and Methods:A community-based cross-sectional study was carried out in Ahmedabad city, Gujarat, India. One ward from each zone of the city was selected by stratified sampling. All individuals above 20 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In India, a cross-sectional study conducted in Ahmadabad city showed that religious practices (78.4%), yoga (11.6%), and meditation (4.8%) are the most popular stress relieving practices. [ 27 ] Hence, we recommend further studies to find out the role played by various adherence factors in yoga practices, emphasizing on modern lifestyle components.…”
Section: Discussionmentioning
confidence: 99%
“…In India, a cross-sectional study conducted in Ahmadabad city showed that religious practices (78.4%), yoga (11.6%), and meditation (4.8%) are the most popular stress relieving practices. [ 27 ] Hence, we recommend further studies to find out the role played by various adherence factors in yoga practices, emphasizing on modern lifestyle components.…”
Section: Discussionmentioning
confidence: 99%
“…It is hope that helping professionals will come to understand the proper uses and potential benefits of Progressive Muscles Relaxation. 37 Ghafari S. et al (August, 2009) had done -a quasi experimental research study on -Effectiveness of applying progressive muscle relaxation technique for quality of life of patients with multiple sclerosis at Fasa, Iran.‖ Study concluded as Progressive Muscle Relaxation Technique is practically feasible and is associated with increase of life quality of multiple sclerosis patients; so that health professionals need to update their knowledge about Progressive Muscle Relaxation Technique as complementary therapies. 38 Max G Feirstein (2009) a dissertation thesis of -a quasi experimental investigation, ‗Moderate effects of worry on group-induced relaxation states' in Australia.‖ An experimental study was to determine whether the characteristics of absorption or worry would moderate by the effects of progressive muscle relaxation technique or guided imagery delivered to groups.…”
Section: -Literature Review Related To the Effectiveness Of The Progrmentioning
confidence: 99%